The Costa Rican women's movement a reader (Pitt Latin American series, 1997)
"Thirty-four short contributions make this akin to a reference work, albeit one varying greatly in flavor, topic, and scholarliness, i.e., from group self-promotion to politico-legal endorsements to scholarly pieces. Among the scholarly topics: colonial women, 19th-century women, feminist organizational theorizing, popular music, caesarean births, and women at the Univ. de Costa Rica (where they are one-third of faculty). Almost all social-feminist topics are touched on, save perhaps language; sexuality, violence, disability, class/race/gender, art and artists, and more"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/